2009
DOI: 10.1037/a0015827
|View full text |Cite
|
Sign up to set email alerts
|

Defining distinct negative beliefs about uncertainty: Validating the factor structure of the Intolerance of Uncertainty Scale.

Abstract: This study examined the factor structure of the English version of the Intolerance of Uncertainty Scale (IUS; French version: M. H. Freeston, J. Rhéaume, H. Letarte, M. J. Dugas, & R. Ladouceur, 1994; English version: K. Buhr & M. J. Dugas, 2002) using a substantially larger sample than has been used in previous studies. Nonclinical undergraduate students and adults from the community (M age = 23.74 years, SD = 6.36; 73.0% female and 27.0% male) who participated in 16 studies in the Anxiety Disorders Laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
171
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(195 citation statements)
references
References 56 publications
7
171
1
9
Order By: Relevance
“…Por otra parte, el análisis factorial indica la emergencia de dos factores (ver Tabla 3), lo cual está en concordancia con los resultados de estudios anteriores en los que también se observaron dos factores que explican la estructura interna de la EII (González Rodrí-guez et al, 2006;Sexton & Dugas, 2009b). No obstante, se han encontrado leves diferencias con el aná lisis de Sexton y Dugas (2009b), especialmente con los ítemes referidos a incertidumbre expresa, que mientras en su estudio cargan en el factor principal, en el presente saturan en el segundo factor.…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…Por otra parte, el análisis factorial indica la emergencia de dos factores (ver Tabla 3), lo cual está en concordancia con los resultados de estudios anteriores en los que también se observaron dos factores que explican la estructura interna de la EII (González Rodrí-guez et al, 2006;Sexton & Dugas, 2009b). No obstante, se han encontrado leves diferencias con el aná lisis de Sexton y Dugas (2009b), especialmente con los ítemes referidos a incertidumbre expresa, que mientras en su estudio cargan en el factor principal, en el presente saturan en el segundo factor.…”
Section: Discusión Y Conclusionesunclassified
“…Es una disposición característica del sujeto que la padece, que resulta de un conjunto de creencias negativas sobre la incertidumbre y sus implicancias (Koerner & Dugas, 2008;Sexton & Dugas, 2009b).…”
Section: Introductionunclassified
“…Recent studies, however, have found associations between IU and symptoms of obsessive-compulsive disorder (OCD; Fergus & Wu, 2010), social phobia (Boelen & Reijntjes, 2009;Carleton, Collimore, & Asmundson, 2010), panic disorder Sexton and Dugas, 2009;, post-traumatic stress disorder (PTSD; Fetzner et al, 2013) and depression (Yook, Kim, Suh & Lee, 2010). Despite many studies linking IU to psychopathology, questions remain about the specific nature of the construct and how it may contribute to psychopathological symptoms (Birrell, Meares, Wilkinson & Freeston, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…First, confirmatory factor analyses were used to select the optimal model of the IUS based on the factor structures. Six alternative models, which have been previously proposed in the literature (Buhr & Dugas, 2002;Carleton, et al, 2007;de Bruin, et al, 2006;Freeston, et al, 1994;Sexton & Dugas, 2009), were tested using the calibration sample. Standardized scores on the constructs were estimated.…”
Section: Statistical Strategymentioning
confidence: 99%
“…However, the factor structures in the cross-cultural study were not consistent among groups, with the considerably correlated factors suggesting that IU should best be interpreted as a unidimensional construct (Norton, 2005). Subsequently, Sexton and Dugas (2009) reinvestigated the factor structure of the English IUS, using larger samples. Exploratory factor analysis (EFA) identified two factors: (1) Uncertainty has negative behavioural and self-referent implications, and (2) Uncertainty is unfair and spoils everything, which were substantiated by confirmatory factor analysis (CFA).…”
Section: Introductionmentioning
confidence: 99%